The Effect of Emotional Intelligence on Work-Related Psychological Health Among Anglican Clergy in Wales - Francis, Leslie J. (Journal of religion and health, 2019)
This study explores the effect of emotional intelligence (assessed by the Schutte Emotional Intelligence Scale) on work-related psychological health (assessed by the two scales of the Francis Burnout Inventory) among 364 Anglican clergy serving in the Church in Wales (264 clergymen, 93 clergywomen, and 7 who did not disclose their sex). After controlling for personal factors (sex and age) and for personality dimensions (extraversion, neuroticism, and psychoticism), the data suggested that higher levels of emotional intelligence enhanced work-related psychological health both in terms of lowering negative affect (emotional exhaustion in ministry) and in terms of increasing positive affect (satisfaction in ministry). These findings suggest that there may be benefits in professional development programmes designed to develop emotional intelligence among clergy.